2012
DOI: 10.5429/2225-0301.2011.03
|View full text |Cite
|
Sign up to set email alerts
|

Challenges facing musical engagement and taste in digitality

Abstract: The ways in which technology mediates the relationship between people and music has increasingly evolved since the advent of playback devices. With the arrival of digital music, and its inherent culture of digitality, new issues have emerged regarding musical engagement at the level of fan and/or consumer. This paper will explore what and where people are engaging with music, as mediated by technology. These two issues will be categorized by: (1) the immense quantity of popular music available digitally is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…For instance, Pettijohn II, LaPiene, Pettijohn, and Horting (2012) suggested that older individuals may use SNS to a lesser degree than younger individuals perhaps because of less familiarity with the technology or a focus on different social goals. Moreover, youth are more likely to use mobile devices and the internet to listen to music than adults (Avdeeff, 2011(Avdeeff, , 2014. SNS adoption rates by older individuals continue to increase (Greenwood, Perrin, & Duggan, 2016), although SNS sites are still most popular with 18-29-year-olds (Brenner & Smith, MUSIC ACTIVITIES ON FACEBOOK, 9 2013; Greenwood et al, 2016;Smith & Anderson, 2018), corresponding to a period when music has been found to be very important to people (Tarrant, North, & Hargreaves, 2002).…”
Section: Understanding How Central Digital Media Including Social Mementioning
confidence: 99%
“…For instance, Pettijohn II, LaPiene, Pettijohn, and Horting (2012) suggested that older individuals may use SNS to a lesser degree than younger individuals perhaps because of less familiarity with the technology or a focus on different social goals. Moreover, youth are more likely to use mobile devices and the internet to listen to music than adults (Avdeeff, 2011(Avdeeff, , 2014. SNS adoption rates by older individuals continue to increase (Greenwood, Perrin, & Duggan, 2016), although SNS sites are still most popular with 18-29-year-olds (Brenner & Smith, MUSIC ACTIVITIES ON FACEBOOK, 9 2013; Greenwood et al, 2016;Smith & Anderson, 2018), corresponding to a period when music has been found to be very important to people (Tarrant, North, & Hargreaves, 2002).…”
Section: Understanding How Central Digital Media Including Social Mementioning
confidence: 99%